The historical evolution of world-systems - Chase-Dunn, Christopher K.; Anderson, E. N. (Eugene Newton), Jr., 1941- (Evolutionary processes in world politics series., 2005)
The rise and decline of great powers remains a fascinating topic of vigorous debate. This book brings together leading scholars to explore the historical evolution of world systems through examining the ebb and flow of great powers over time, with particular emphasis on early time periods.